PENGARUH MOTIVASI KERJA, KEPEMIMPINAN KEPALA SEKOLAH, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SMA MUHAMMADIYAH DI WILAYAH BANDUNG RAYA - Burhanudin, Burhanudin; Santosa, Achadi Budi; Sukirman, Sukirman (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The objective of this study is to determine the influence of work motivation, school principal leadership, and work environment on the performance of Muhammadiyah Senior High School teachers in the Greater Bandung area. This study employs a quantitative approach, where research data is presented in numerical form, and the analysis tool utilizes statistics with a descriptive-verificative method. This method is used to examine the influence or causal relationship of the studied issue, namely determining the extent to which work motivation, school principal leadership, and work environment affect the performance of Muhammadiyah Senior High School teachers in the Greater Bandung area. The results of this study indicate that work motivation has a significant influence on the performance of Muhammadiyah Senior High School teachers in the Greater Bandung area, with a total effect of 30.4%. The school principal's leadership has the most significant influence on teacher performance, with a total effect of 32.5%. The work environment also has a significant influence on teacher performance, with a total effect of 23.3%. Simultaneously, work motivation, school principal leadership, and work environment significantly influence the performance of Muhammadiyah Senior High School teachers in the Greater Bandung area, with a total effect of 41.5%, while the remaining 58.5% is influenced by other factors not examined in this study.